O ensino de Sociologia para além do estranhamento e da desnaturalização: por uma percepção figuracional da realidade social - Bodart, Cristiano das Neves (Latitude, 2021)
O artigo problematiza as formas de apropriação dos conceitos de desnaturalização e estranhamento presentes nas OCEM-Sociologia (2006) que, quando destacados, tornam-se as especificidades da Sociologia escolar. Argumenta-se que: i) a Sociologia escolar carece de abordagens propositivas de orientação à prática docente; ii) o “olhar figuracional da vida social” é uma disposição epistemológica potente para descrever as especificidades da Sociologia escolar; iii) a clareza das especificidades da Sociologia é de suma importância para sua consolidação enquanto disciplina do Ensino Básico. Para tanto, realiza-se uma breve revisão de literatura e apropria-se das contribuições de autores contemporâneos, sobretudo Norbert Elias, para uma proposição de especificidade da Sociologia escolar, sendo o “olhar figuracional da realidade social”. Abstract The article discusses the forms of appropriation of the concepts of denaturalization and the strangeness present in the OCEM-Sociology (2006) when highlighted being the specificities of school Sociology. It is argued that: i) school sociology lacks propositional approaches to guide teaching practice; ii) the “figurational look at social life” is a powerful epistemological disposition to describe the specifics of school sociology; iii) the clarity of the specificities of Sociology is of paramount importance for its consolidation as a Basic Education discipline. To this end, a brief literature review is carried out and the contributions of contemporary authors, especially Norbert Elias, are appropriated for a specific proposition of school sociology, being the “figurational look of social reality”. Palavras-chave: Ensino de Sociologia. Configuração. Desnaturalização. Estranhamento. Abstract The article questions the ways of appropriating the concepts of denaturalization and the strangeness present in the OCEM-Sociology (2006) when highlighted being the specificities of school Sociology. It is argued that: i) school sociology lacks propositional approaches to guide teaching practice; ii) the "figurational perception of social life" is a more coherent epistemological disposition to describe the specificities of school sociology; iii) the clarity of the specificities of Sociology is of paramount importance for its consolidation as a Basic Education discipline. To this end, a brief review of the literature is carried out and the contributions of contemporary authors, especially Norbert Elias, are appropriated for a proposal regarding the specificity of school sociology, being the "figurational perception of social reality". Keywords: Teaching Sociology. Configuration. Denaturation. Estrangement.